The relationship between circulating irisin, retinol binding protein-4, adiponectin and inflammatory mediators in patients with metabolic syndrome - Tabak, Omur; Simsek, Gonul; Erdenen, Fusun; Sozer, Volkan; Hasoglu, Tuna; Gelisgen, Remise; Altunoglu, Esma; Muderrisoglu, Cuneyt; Senyigit, Abdulhalim; Uzun, Hafize (SBEM-SOC BRASIL ENDOCRINOLOGIA & METABOLOGIA, 2017)
Objective: We wanted to investigate whether there is a relationship between circulating irisin, retinol binding protein-4 (RBP-4), adiponectin and proinflammatory mediators implicated in the development of insulin resistance (IR) in metabolic syndrome (MetS). Subjects and methods: In 180 individuals, including controls and patients with MetS, we measured fasting plasma insulin, high sensitivity C-reactive protein (hsCRP), pentraxin-3 (PTX-3), interleukin-33 (IL-33), irisin, RBP-4, and adiponectin using ELISA kits. Results: While fasting plasma hsCRP, PTX-3, IL-33, irisin, RBP-4 concentrations were higher, adiponectin levels were lower in patients with MetS than in controls. A correlation analysis revealed that plasma irisin levels were positively associated with MetS components such as waist circumference and waist-hip ratio, low density lipoprotein (LDL) and markers of systemic inflammation such as PTX-3, hsCRP, uric acid, and RBP-4. Adiponectin levels were negatively associated with waist circumference, waist-hip ratio, PTX-3 and LDL. Conclusions: Although the precise mechanisms are still unclear, irisin, RBP-4, adiponectin and PTX-3 are hallmarks of the MetS, which is related to low-grade inflammation. It is conceivable that irisin and adiponectin might contribute to the development of MetS and may also represent novel MetS components. Future clinical studies are needed to confirm and extend these data.
Keywords: Metabolic syndrome; high sensitivity C-reactive protein; pentraxin-3; interleukin-33; irisin; retinol binding protein-4; adiponectin; TYPE-2 DIABETES-MELLITUS; PLASMA PENTRAXIN 3; INSULIN-RESISTANCE; ASSOCIATION; ADIPOKINES; PTX3; RBP4; Endocrinology & Metabolism